Thermosonication-assisted fortification of kiwi juice with bee bread: enhancing nutritional and functional properties through ANFIS-RSM optimization - Yıkmış, Seydi; Duman Altan, Aylin; Türkol, Melikenur; Tokatlı, Nazlı; Yıldırım Maviş, Çiğdem; Tokatlı Demirok, Nazan; Aadil, Rana Muhammad; Karrar, Emad; Aljobair, Moneera O.; Mohamed Ahmed, Isam A. (Frontiers in Nutrition, 2025)
This study investigated the effects of thermosonication on the preservation and enhancement of bioactive components in kiwi juice fortified with bee bread. Response Surface Methodology (RSM) and Adaptive Neuro-Fuzzy Inference System (ANFIS) were employed to optimize processing parameters by evaluating FRAP, total phenolics, total chlorophyll, and ascorbic acid levels. Thermosonication significantly enhanced the levels of phenolic compounds (127.97 GAE mg/100 mL) and ascorbic acid (14.89 mg/100 mL), while a reduction in chlorophyll content was observed. The ANFIS model provided more accurate predictions compared to RSM, particularly under optimal processing conditions. Additionally, the thermosonication-treated kiwi juice with bee bread (TS-KJB) exhibited the highest antioxidant capacity, total flavonoid, and dietary fiber content. The findings demonstrate that thermosonication is an effective and sustainable technique for improving the functional and nutritional properties of bee bread-fortified kiwi juice. This approach offers a promising alternative for the production of additive- and preservative-free functional fruit juices.